Molecular Mimicry between Respiratory Syncytial Virus F Antigen and the Human Proteome - Kanduc, Darja (Global Medical Genetics, 2023)
This study examined respiratory syncytial virus (RSV) F glycoprotein (gp) antigen for molecular mimicry with the human proteome. It was found that the viral antigen presents an impressive number of pentapeptides (namely, 525 out of 570) in common with the human proteome, with viral sequences widely and repeatedly distributed among 3,762 human proteins implicated in crucial fundamental cellular functions. The data can have implications for anti-RSV vaccines. Indeed, the high level of molecular mimicry can lead to cross-reactivity and autoimmunity, and invites to follow safer vaccinal protocols based on pentapeptide sequences uniquely present in the viral antigen.
Keywords: molecular mimicry; RSV F; anti-RSV vaccines